2+(-9)-(-4)=

Simple and best practice solution for 2+(-9)-(-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+(-9)-(-4)= equation:


2+(-9)-(-4)=0

We simplify the equation to the form, which is simple to understand
2+(-9)-(-4)=0

Remove unnecessary parentheses
+2-9-(-4+)=0

Remove unnecessary parentheses
2-9+4=0

We move all terms containing to the left and all other terms to the right.
0=0-2+9-4

We simplify left and right side of the equation.
0=+3

0=3

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| -69=7v-5 | | (r+5/3)=20 | | -6y-2=3-5y | | 4m+8+5(3m-5)-5(m+5)=0 | | 2y-6=5y+6 | | (X-3)x=550 | | 7-3x=7-4x+x | | 2x-2=18x+6 | | 30+34-x=13x-5x+37 | | 2z+5=4x-9 | | 1-(-4-n)=3(n+3) | | 5x^2+20xy-40y= | | 9-(-9)+(-4)= | | x+2x+6x+3=21 | | 4y^3-5y^2-12y+15= | | Y(7+3)=5 | | (-7)+2+(-5)= | | -2(1-3x)-x=-2-6x | | 4y^3-5y^2-12y-15= | | 5(a-12)+(2a+15)=a-9 | | 8x-7x=-(1-2x)-7(x+5) | | 5/3x-5=3x+7 | | (-8)-7-(-2)= | | 3x=82+1x | | 2p-9p=49 | | 9n^2-9= | | 7(7-2x)-6=-5(-8+4x)-3 | | y=58-4z | | 5x^4-7x^2=-2 | | 4=6x-2(2x-7) | | 1184=16t^2 | | (-1)-(-2)-9= |

Equations solver categories